2003
DOI: 10.1021/tx034022l
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Deuterium Substitution Attenuates the Tumorigenicity and Metabolism of the Tobacco-Specific Nitrosamine 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK)

Abstract: Stereochemical determinants of the tumorigenicity and metabolism of the tobacco-specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) were investigated using the stereospecifically deuterated isotopomers (4R)-[4-(2)H(1)]NNK and (4S)-[4-(2)H(1)]NNK. Upon ip administration to groups of 20 female A/J mice, NNK and (4S)-[4-(2)H(1)]NNK exhibited similar lung tumorigenicity at three different doses, whereas (4R)-[4-(2)H(1)]NNK was 2-fold less tumorigenic at all three doses. In a parallel experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…Lung tumor multiplicity is highly correlated with levels of persistent O 6 -methyl-dGuo in DNA (22). This DNA adduct causes G f A mutations in codon 12 of the k-ras oncogene leading to lung tumor formation (23,24 (21). Earlier, we demonstrated a high correlation between persistent O 6 -methyl-dGuo in this model and the number of lung tumors per mouse, as well as the presence of G f A transition mutations in the k-ras gene isolated from the lung tumors (22,23).…”
Section: Tobacco-specific Nitrosamines: Metabolism Dna Adduct Formatmentioning
confidence: 74%
See 1 more Smart Citation
“…Lung tumor multiplicity is highly correlated with levels of persistent O 6 -methyl-dGuo in DNA (22). This DNA adduct causes G f A mutations in codon 12 of the k-ras oncogene leading to lung tumor formation (23,24 (21). Earlier, we demonstrated a high correlation between persistent O 6 -methyl-dGuo in this model and the number of lung tumors per mouse, as well as the presence of G f A transition mutations in the k-ras gene isolated from the lung tumors (22,23).…”
Section: Tobacco-specific Nitrosamines: Metabolism Dna Adduct Formatmentioning
confidence: 74%
“…Human P450s 2A13 and 2B6, rat P450 2A3, and mouse P450 2A5 may be the most important catalysts of NNK metabolic activation in these species, based on their kinetic parameters. The critical role of mouse P450 2A5 has been clearly shown by deuterium-labeling studies, which demonstrated the stereoselective abstraction of the 4(R)-hydrogen of NNK, leading to a cascade of events resulting in lung tumor induction in A/J mice (21) (Figure 1 (21). The initially formed intermediate shown here is converted to R-methylene-hydroxyNNK (7, Scheme 1), which spontaneously yields methanediazohydroxide and the methyl diazonium ion (shown).…”
Section: Tobacco-specific Nitrosamines: Metabolism Dna Adduct Formatmentioning
confidence: 99%
“…Although in that study DNA adducts were not investigated, NNK, a tobacco-specific lung carcinogen, is known to function by initiating a cascade of reactions that results in production of the adduct O 6 -methylguanine, among other DNA adducts (49). A strong correlation between persistent O 6 -methylguanine levels in pulmonary DNA and lung tumors has been observed in mice (50). At this point, it is probably worth studying more in detail the relationship among Fhit protein, DNA adducts of different types, and lung tumor incidence in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Lung tumor formation was induced with NNK according to the protocol of Jalas et al (12). All animals, at the age of 2 months, with or without the doxycycline treatment from E0, were given a single i.p.…”
Section: Methodsmentioning
confidence: 99%
“…NNK-induced lung carcinogenesis is believed to occur via P450-mediated a-hydroxylation, which leads to production of reactive metabolites that induce the formation of DNA adducts, including O 6 -methylguanine (O 6 -mG; refs. 10,12). The in vivo role of P450 in NNK-induced carcinogenesis has been indicated in studies using structurally diverse P450 inhibitors (10,(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%